KONSEP INTEGRATION LAYER DALAM PEMBANGUNAN DATA WAREHOUSE - PULANTARA, I WAYAN; SANTIYASA, I WAYAN (Jurnal Matematika, 2012)
Information availability in exact time is one of keys for correct decision making. One of the solutions is by developing a Data Warehouse for supporting decision making. In general Data Warehouse contains Dependent Data Mart (DDM), Integration Layer(IL), and Extract- Transform-Load (ETL). Integration Layer is a database that contains data that already integrated, stored in aid for one or more decision support system. For its data source, integration layer require Extract-Transform-Load (ETL) as supplier for clean and integrated data. Integration Layer volume would be much larger than any on dependent data mart that its support, so the focus aspect in developing Integration Layer as core part of Data Warehouse is how to handle a huge amount of data in considerable performance. Beside that, interfacing aspect is also important, e.g. how Integration Layer interact with ETL Process and supporting dependent data.
Keywords: Reporting System, Data Warehouse, Dependent Data Mart, Integration Layer, Extract-Transform-Load (ETL), Performance